Konservatisme akuntansi ditinjau dari agency conflict antara pemegang saham, kreditor dan manajemen - Sudane, Gede Agus; Endiana, I Dewa Made; Pramesti, I Gusti Ayu Asri (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2020)
The principle of conservatism is a concept that recognizes burdens and obligations as soon as possible despite the uncertainty about the results, but only recognizes income and assets when it is certain to be received. Based on the conservatism principle, if there is uncertainty about losses, the company must tend to record losses. Conversely, if there is uncertainty about profits, the company does not have to record profits. As such, profit statements tend to produce lower total profits and asset values just in case. This study aims to reexamine the effect of conflicts between shareholders and creditors and conflicts between shareholders and management. The sample in this study is manufacturing companies listed on the Indonesia stock exchange period 2017 to 2019. Determination of the sample using a purposive sampling method. Based on purposive sampling obtained 23 companies that meet the sample criteria. Conflicts between shareholders and creditors are measured using the DPR, ROA, and DER proxies, and conflicts between shareholders and management are measured using KI and KM proxies. The analytical tool used is multiple linear regression analysis. The results showed that the conflict variable between shareholders and creditors had no effect and the conflict between shareholders and management had a negative effect.